Innovative Model to Strengthen Human Rights Protection in Indonesia’s 2026 National Criminal Code - R Arif Sulaiman; Nabil Librian Pratama (Manunggal Halim Jaya, 2026)
This study analyzes the legal framework for the protection of human rights within the Indonesian legal system and its reinforcement in the 2026 National Criminal Code (KUHP). It employs a normative legal research design using a literature review method, integrating both statutory and contextual approaches to enhance methodological transparency and facilitate future replication. The research adopts a qualitative approach through library research. Data are derived from primary legal materials, including the 2026 National Criminal Code, human rights related legislation, and international human rights instruments, as well as secondary legal materials such as books and relevant academic journals. The sources are selected through purposive sampling based on academic relevance. Data are analyzed using a descriptive-qualitative approach by examining the relationship between criminal law norms and human rights principles, and by comparing them with legal doctrines and practices in several countries, drawing on the theoretical frameworks of human rights, legal protection, and criminal law policy. The findings indicate that strengthening human rights principles within the Criminal Code has the potential to enhance the effectiveness of a more just and humane criminal justice system. These findings also have important implications for future legal research and policy-making, particularly in improving the implementation of human rights standards and strengthening institutional accountability in Indonesia.